The Management of Facilities and Infrastructure in the Development of Islamic Boarding Schools in Jambi Province - Muhamad Toyib; Muntholib Muntholib; Edi Kusnadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is motivated by the condition of Islamic boarding schools in Jambi province in terms of infrastructure management. The research objective is to determine the infrastructure management system in developing Islamic boarding schools in Jambi Province.The research method uses a qualitative approach. The sample in this study; Nurul Jalal Islamic boarding school, Tebo Regency City, Zulhijjah Islamic boarding school, Batang Hari Regency, Nurul Iman Islamic boarding school, Jambi City and as a research informant for Islamic boarding school leaders, madrasa leaders and staff who handle infrastructure management. Data collection technique using snowball sampling. Sampling technique using the method : interviews, documentation, observation. To test the validity of the data by using data triangulationThe research results are as follows; first, management of facilities and infrastructure in the development of Islamic boarding schools in Jambi Province, the Islamic boarding schools as samples in this research are as follows; carry out planning, carry out implementation and organization, then carry out the process of procurement and inventory of facilities and infrastructure as well as the final stage of monitoring and evaluating the condition of infrastructure in an effort to develop Islamic boarding schools. All activities are oriented towards achieving goals, clarity and responsibility, administration, efficiency and consistency in the use of facilities and infrastructure. Second, the inhibiting factors in the process of managing facilities and infrastructure to develop Islamic boarding schools in Jambi province include; human resources, educational funds as well as the location and geography of Islamic boarding schools, while the supporting factors in managing facilities and infrastructure in developing Islamic boarding schools in Jambi Province come from the culture of Islamic boarding schools and the principles possessed by Kiai as leaders of Islamic boarding schools. Third, the efforts made by Islamic boarding schools in managing facilities and infrastructure in developing Islamic boarding schools in Jambi Province include; maximizing the allocation of the use of education financing funds for facilities and infrastructure, increasing human resources through training, collaborating with other institutions, collaborating with the private sector, collaborating with the government and the community. Fourth, a suitable management model for facilities and infrastructure in developing Islamic boarding schools in Jambi Province, the results of findings in the field show a model that is more suitable for developing Islamic boarding schools. The facilities and infrastructure management model is carried out using a strategic management model and at the beginning of activities uses the active management concept. This activity is influenced by the type and style of Islamic boarding school leadership. Apart from that, Islamic boarding school leaders view facilities and infrastructure as resources in the form of sources of strength in achieving a goal and as resources related to humans, finances and materials.